2009
DOI: 10.1007/s00421-009-1304-2
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary activation of the ankle plantar flexors following whole-body vibration

Abstract: This study investigated the effect of whole-body vibration (WBV) on the voluntary activation of the ankle plantar flexors. Twelve healthy young adults were randomly exposed to two treatments on separate occasions. The first (non-WBV) involved stretching of the plantar flexors at end range of dorsiflexion for five 1-min bouts. The second involved the same stretch with WBV (26 Hz) for five 1-min bouts. Attempted maximal voluntary contractions (AMVCs) of the plantar flexors were performed on an isokinetic dynamom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
1
9
1
Order By: Relevance
“…However, the lack of change in torque suggests that this artifact had a limited impact on the similar torque-angle relationship measured after intervention. These findings contrast with reports from Kemertzis et al (2008) and Pellegrini et al (2010) showing a shift in plantarflexor peak torque angle towards a longer muscle length after a single session of WBV. Regardless of mechanisms explaining this shift, these studies indicate that WBV constitutes a sufficient stimulus to alter the torque-angle relation in plantarflexor muscles.…”
Section: Torque-angle Relationshipcontrasting
confidence: 99%
See 3 more Smart Citations
“…However, the lack of change in torque suggests that this artifact had a limited impact on the similar torque-angle relationship measured after intervention. These findings contrast with reports from Kemertzis et al (2008) and Pellegrini et al (2010) showing a shift in plantarflexor peak torque angle towards a longer muscle length after a single session of WBV. Regardless of mechanisms explaining this shift, these studies indicate that WBV constitutes a sufficient stimulus to alter the torque-angle relation in plantarflexor muscles.…”
Section: Torque-angle Relationshipcontrasting
confidence: 99%
“…One may speculate that increasing the intensity of the stimulus transmitted to the quadriceps, by altering vibration parameters, would have yielded similar results to that of Kemertzis et al (2008) and Pellegrini et al (2010). Furthermore, the patellar tendon was selected for the present experiment in accordance with our previous report about WBV training.…”
Section: Torque-angle Relationshipmentioning
confidence: 96%
See 2 more Smart Citations
“…1,2 Researchers have demonstrated that WBV can improve aspects of physical performance, such as strength [3][4][5] and flexibility, 6,7 whereas evidence regarding the physiologic changes associated with therapeutic WBV remains unclear. [8][9][10][11][12] The influence of WBV on peripheral blood flow and muscle oxygen use is of special interest, as these measures provide insight into the metabolic changes occurring in skeletal muscle.…”
mentioning
confidence: 99%